Psychometric Analysis of Student Social Skill Instruments (S3I) with the Rasch Model - Fatimah, Siti; Ahman, Ahman; Suherman, Uman; Ilfiandra, Ilfiandra; Annisa, Dona Fitri (Bulletin of Counseling and Psychotherapy, 2025)
Social skills are an important aspect in developing the character of 21st century students, especially in facing the challenges of communication, collaboration, and cross-cultural interaction. However, there is no measurement instrument specifically designed to assess students' social skills in the context of higher education in Indonesia. This study aims to develop and evaluate a valid, reliable, and gender- and department-free Student Social Skills Instrument (S3I). The research sample consisted of 575 responses collected from various departments at IKIP Siliwangi, consisting of 113 male students (19.7%; SD = -0.79) and 462 female students (80.3%; SD = 0.69). The S3I instrument consists of 204 items arranged on a 5-point Likert scale. Data analysis was conducted using the Rasch model approach, including analysis of item validity, reliability, unidimensionality, and Differential Item Functioning (DIF) based on gender and department. The results showed that the S3I instrument had very high reliability (α = 0.98), met the criteria of unidimensionality (explained variance 29.8%), and most of the items showed conformity with the Rasch model. However, some items were found to be inappropriate and biased towards certain genders or majors, so they needed to be revised further. Overall, the S3I was stated as an appropriate and accurate measuring instrument to assess students' social skills in the context of higher education.